MicroCT illuminates the unique morphology of Shiinoidae (Copepoda: Cyclopoida), an unusual group of fish parasites - Bernot, James P.; Boxshall, Geoffrey A.; Goetz, Freya E.; Phillips, Anna J. (PeerJ, 2024)
The copepod family Shiinoidae Cressey, 1975 currently comprises nine species of teleost parasites with unusual morphology and a unique attachment mechanism. Female shiinoids possess greatly enlarged antennae that oppose a rostrum, an elongate outgrowth of cuticle that originates between the antennules. The antennae form a moveable clasp against the rostrum which they use to attach to their host. In this study, we use micro-computed tomography (microCT) to examine specimens of Shiinoa inauris Cressey, 1975 in situ attached to host tissue in order to characterize the functional morphology and specific muscles involved in this novel mode of attachment and to resolve uncertainty regarding the segmental composition of the regions of the body. We review the host and locality data for all reports of shiinoids, revise the generic diagnoses for both constituent genera Shiinoa Kabata, 1968 and Parashiinoa West, 1986, transfer Shiinoa rostrata Balaraman, Prabha & Pillai, 1984 to Parashiinoa as Parashiinoa rostrata (Balaraman, Prabha & Pillai, 1984) n. comb., and present keys to the females and males of both genera.
Keywords: Copepod; Parasite; Functional morphology; MicroCT; Cyclopoida; Rostrum; Attachment; Fish; Scombridae; Scomberomorus